PENGARUH PERSEPSI RESPONS PENANGANAN KRISIS DAN KETEPATAN PROGRAM TERHADAP REPUTASI PT. PERTAMINA (PERSERO) PADA KASUS OPLOSAN PERTAMAX - Akbar Raushan Fikri; Agus Naryoso (Interaksi Online, 2026)
The issue of alleged adulteration of Pertamax fuel involving PT. Pertamina (Persero) has generated various public perceptions that may affect the company’s reputation. The problem lies in the diverse public evaluations of Pertamina’s crisis response and the appropriateness of the programs implemented. This study aims to analyze the effect of perceived crisis response and program appropriateness on Pertamina’s reputation in the context of the alleged Pertamax adulteration issue. This research employs a quantitative approach based on Situational Crisis Communication Theory (SCCT). Data were collected through online questionnaire, selected using purposive sampling. Data analysis was conducted using multiple linear regression, supported by validity, reliability, classical assumption, and hypothesis testing. The results show that perceived crisis response and program appropriateness have a positive and significant effect on Pertamina’s reputation, both partially and simultaneously. Furthermore, the coefficient of determination test shows an R Square value of 0,575, indicating that 57,5% of the variation in reputation is explained by perceived crisis response and program appropriateness, while the remaining 42,5% is influenced by other factors outside this study.